Case report: A case of immune thrombocytopenia combined with Hashimoto's thyroiditis and Helicobacter pylori infection in a child - Yang, Lihong; Xiao, Dongqiong; Li, Xihong; Lai, Chunqi; Chen, Yuhao; Pan, Lingli (Frontiers in Pediatrics, 2023)
Immune thrombocytopenia is a common immune-mediated bleeding disorder in children, occurring in 5 to 10 percent of every 100,000 children each year, and is primarily characterized by an isolated decrease in platelet count(1, 2). ITP can be divided into two subtypes: primary ITP and secondary ITP. Studies in most developed countries show that 80% of ITP cases are primary ITP and the remaining 20% are secondary ITP. However, studies from developing countries have shown that secondary ITP occurs more frequently than primary ITP(3). According to literature reports, the immune response of B cells and T cells plays an important role in the pathogenesis of ITP(4). It has been found that H. pylori infection can cause ITP and lead to a variety of autoimmune diseases(5). Here, we present the case of an 11-year-old patient who presented with immune thrombocytopenia, Hashimoto's thyroiditis, and H. pylori infection. After anti-H. pylori treatment and thyroxine supplementation, the platelet count increased compared to the previous one. Therefore, we recommend early screening for thyroid function and H. pylori and timely early intervention for the treatment and prognosis of children with immune thrombocytopenia.